Continuing vocational training in times of economic uncertainty: An event-study analysis in real time - Christine Dauth; Julia Lang (Journal for Labour Market Research, 2024)
Continuing vocational training (CVT) is a key channel for employees to adapt their skills to changing requirements in the labor market due to structural changes and digitization. The COVID-19 pandemic and the energy crisis as a consequence of the war in Ukraine may have accelerated these developments. Yet, it is unclear how the economic impact of these crises affects individuals' occupational preferences. In this study, we want to investigate how interest in CVT changes in times of economic uncertainty. We use Google Trends data for Germany and apply an event study analysis to examine how interest in CVT developed with the onset of the COVID-19 pandemic and the Russian attack on Ukraine. We find that the interest in CVT strongly declined during the first wave of the pandemic regardless of how severely a region was affected. During the second lockdown, the decline in CVT interest was more pronounced in the eastern German states where we find a general decline in search intensity since March 2020. We also consider different channels that may have influenced the demand for CVT during the pandemic. Overall, we show that during the first 2.5~years of the pandemic, the search intensity for CVT decreased on average by 12 to 19 percent, while the search intensity for online CVT increased by 39 to 45 percent. We also see a decrease in the search intensity for CVT at the beginning of the energy crisis.
Keywords: J24; I18; 330; COVID-19 pandemic; Continuing vocational training; Energy crisis; Online training